Effect Of Workload, Work Stress and Competency on Job Satisfaction and Auditor Performance at The Inspectorate of East Java Province - Hidayati, Ani Wahyu; Mujanah, Siti; Budiarti, Endah (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This research intends to investigate the impact of workload, job stress, and competence on job satisfaction and performance of auditors at the East Java Inspection Service. The quantitative approach is used in current research, and then the data is generated by means of a questionnaire which is further analyzed by partial least squares (PLS). The population consisted of 70 auditors who were employed. This study resulted in a significant impact of workload on job satisfaction and auditor performance in a negative direction, then work stress had a significant impact on satisfaction in a negative direction but had no significant impact on auditor performance. In addition, there is a significant impact of competence on work performance in a positive way. Furthermore, satisfaction has an impact on the performance of the examiner at the East Java Provincial Inspectorate. R Square value of job satisfaction shows 0,409 which means that workload, work stress, and competence to explain changes in the value of the job satisfaction variable was 40.9%. besides, R square value of the construct of auditor performance shows 0,527 means that workload, job stress, competence, and job satisfaction can explain the variance of auditor performance by 52.7%.